2015
DOI: 10.4315/0362-028x.jfp-15-153
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella during Drying of Fresh Ginger Root (Zingiber officinale) and Storage of Ground Ginger

Abstract: The survival of Salmonella on fresh ginger root (Zingiber officinale) during drying was examined using both a laboratory oven at 51 and 60°C with two different fan settings and a small commercially available food dehydrator. The survival of Salmonella in ground ginger stored at 25 and 37°C at 33% (low) and 97% (high) relative humidity (RH) was also examined. To inoculate ginger, a four-serovar cocktail of Salmonella was collected by harvesting agar lawn cells. For drying experiments, ginger slices (1 ± 0.5 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
(20 reference statements)
2
3
1
Order By: Relevance
“…In contrast to the present work, some studies have shown that reduced a w protects against the decrease of Salmonella serovars in low moisture food products (Archer et al, 1998;Doyle & Mazzotta, 2000;Beuchat & Scouten, 2002;Keller et al, 2013;Gradl et al, 2015). Gradl et al (2015) and Keller et al (2013) reported that Salmonella viability decreased during 25 and 37 °C storage of ground ginger and black pepper when a w was about 0.86, however, viability remained relatively stable when the a w of samples was < 0.40. Similarly, Salmonella numbers decreased during 25 and 37 °C storage on alfalfa seeds with an a w of 0.21 to 0.60, but not when stored at 5 °C, as the a w in seeds was increased (Beuchat & Scouten, 2002).…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast to the present work, some studies have shown that reduced a w protects against the decrease of Salmonella serovars in low moisture food products (Archer et al, 1998;Doyle & Mazzotta, 2000;Beuchat & Scouten, 2002;Keller et al, 2013;Gradl et al, 2015). Gradl et al (2015) and Keller et al (2013) reported that Salmonella viability decreased during 25 and 37 °C storage of ground ginger and black pepper when a w was about 0.86, however, viability remained relatively stable when the a w of samples was < 0.40. Similarly, Salmonella numbers decreased during 25 and 37 °C storage on alfalfa seeds with an a w of 0.21 to 0.60, but not when stored at 5 °C, as the a w in seeds was increased (Beuchat & Scouten, 2002).…”
Section: Discussioncontrasting
confidence: 95%
“…Janning et al (17) also found a negligible decrease in culturable Salmonella cells in milk powder that was dried with anhydrous silica gel at 228C for at least 3 months. The findings of the present study are consistent with the a w inactivation kinetics of Salmonella reported previously (12,13).…”
Section: Resultssupporting
confidence: 93%
“…An average of a 0.68 log CFU/g drop was observed between the day of preparation of inoculated flour and the day of use. This initial drop and subsequent Salmonella survival is consistent with observations made in other low a w foods (Keller and others ; Blessington and others ; Gradl and others )…”
Section: Resultssupporting
confidence: 90%